Peran Data Integration Dalam Mewujudkan Interoperabilitas Sistem Informasi - Siregar, Saniyah Dwi Putri; Nasution, Muhammad Irwan Padli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
To ensure the interoperability of information systems, data integration is very important, especially when facing the problem of data fragmentation between units. By conducting a library study of five journals from the public and education sectors, this study aims to spread the role of data integration in supporting the connectivity of information systems. The results of the study indicate that the use of technologies such as DHIS2, SIMPUS, Web Service, and Government Service Bus can improve service coordination, efficiency, and data accuracy. However, for sustainable and optimal interoperability, this integration also requires policy support, governance, and human resource readiness